Reporting incidental findings of genomic disorder-associated copy number variants to unselected biobank participants - Leitsalu, Liis; Alavere, Helene; Jacquemont, Sébastien; Kolk, Anneli; Maillard, Anne M; Reigo, Anu; Nõukas, Margit; Reymond, Alexandre; Männik, Katrin; Ng, Pauline C; Metspalu, Andres (Personalized medicine, 2016)
Procedural guidelines for disclosure of incidental genomic information are lacking. We introduce a method and evaluated the impact of returning results to population biobank participants with 16p11.2 copy number variants, which are commonly associated with neurodevelopmental disorders and BMI imbalance. Of the 7877 participants, 11 carriers were detected. Eight participants were informed of their carrier status and surveyed 11-17 months later. All participants demonstrated preference for disclosure. Although two participants experienced worry, all five survey respondents rated receiving this information favorably. One participant reported modifications in treatment and three felt that their treatment/condition had since improved. This approach can be adapted and applied for the return of incidental findings to biobank participants.